LANGUAGE IDENTITY AND CULTURAL INTEGRATION AMONG RURAL-TO-URBAN UNIVERSITY STUDENTS - Ryan Muhtadi Agha Situmorang; Martha Jenica Br Sitorus; Ajeng Dilla Maisyaroh; Delvi Aulia; Sri Minda Murni; Anna Riana Tambunan (Language Literacy: Journal of Linguistics, Literature, and Language Teaching)
This study examines how university students from rural backgrounds adapt linguistically and culturally after moving to the urban environment of Medan, Indonesia. As these students transition into city-based academic settings, they face the complex task of balancing their cultural roots with the demands of urban life. Guided by Berry’s (2001) Acculturation Theory, this research explores how students navigate issues of identity, language use, and cultural integration. Data were gathered through questionnaires completed by 22 students who had spent at least six semesters studying at a public university in Medan. Through thematic analysis, the study uncovered various adaptation strategies. Most students adopted an integration approach, successfully blending their native language and traditions with urban norms. Some displayed assimilation, especially in formal academic settings, while instances of marginalization were rare. These findings underscore the importance of university policies and support systems that are culturally responsive and inclusive—helping students negotiate their identities and adjust more smoothly to diverse academic environments.